DESIGN OF WELDED JOINTS PROVIDING LOW-CYCLE FATIGUE AT THE LEVEL OF BASE METAL - Vitaly F. Lukyanov; Yury G. Lyudmirskiy; Dmitry V. Rogozin (Advanced Engineering Research)
The test data of welded joints with butt and fillet welds on l ow - cycle fatigue under biaxial tension in the corrosive environment are considered. Some constructive techniques for improving the fatigue strength of welde d joints through changing the weld geometrical parameters are offered.